REGIONAL MECHANISM OF INTERNATIONAL COOPERATION IN THE FIELD OF COMBATING CRIME - Safarov Nurbek Abdivaliyevich (Western European Studies, 2025)
The article analyzes regional mechanisms of international cooperation in the field of combating crime. All conventions, treaties and agreements have been studied by the implementation of special procedural actions, which determine the international cooperation in criminal cases between contracting parties
Keywords: International Cooperation; Council of Europe; European Union